Combined endoscopy-laparoscopy-gastrostomy extraction for Rapunzel syndrome - Hery Poerwosusanta; Pricilia G. Halim; Adrian Sitompul; Agung Ari Wibowo (Elsevier, 2020)
Introduction: Rapunzel syndrome (RS) is an uncommon diagnosis in children with less than 40 cases reported. Open-laparotomy-gastrostomy, as standard treatment, has many risks, while single endoscopy or laparoscopy is quite hard to be performed for too many trichobezoars. We present a case of RS treated successfully with the first combination of endoscopy-laparoscopy-gastrostomy. Case: A 9-year-old girl with episodic abdominal pain, recurrent vomiting, anorexia, constipation, non-tender abdominal enlargement, trichophagia, and trichotillomania was diagnosed as RS from barium meal and endoscopy examination. We performed combined endoscopy-laparoscopy-gastrostomy to remove 400 g of bezoar mass. The patient had a good outcome and a shorter hospital stay. Conclusion: Combined endoscopy-laparoscopy-gastrostomy provide better treatment of choice in a child with Rapunzel syndrome. Key messages: Minimal invasive surgery performed through combined endoscopy-laparoscopy-gastrostomy is the new removal technique for large size trichobezoar.